2021
DOI: 10.1111/btp.12952
|View full text |Cite
|
Sign up to set email alerts
|

Reported climate change impacts on cloud forest ants are driven by sampling bias: A critical evaluation of Warne et al. (2020)

Abstract: Long-term changes in tropical insect communities are largely unknown, in particular for mountain forest ecosystems (Basset & Lamarre, 2019;Chen et al., 2009). This is worrying, given the ongoing environmental changes including those concerning climate. Here, we present a reanalysis of a recent paper by Warne et al., (2020a), in which the authors reported changes in species richness, species composition, phylogenetic diversity, and trait distributions in a cloud forest ant assemblage in response to climate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Empirical evidence showing effects of climate change on other major animal taxa, such as mammals, reptiles and most invertebrates, is too limited to identify any clear patterns. For instance, a resurvey of tropical montane ants in Costa Rica concluded that over a decade, the community became less diverse, with upland areas becoming more similar to lowland ones (Warne et al ., 2020) – suggesting that thermophilisation of communities is not limited to flora – however, this finding was promptly contested (Klimes et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Empirical evidence showing effects of climate change on other major animal taxa, such as mammals, reptiles and most invertebrates, is too limited to identify any clear patterns. For instance, a resurvey of tropical montane ants in Costa Rica concluded that over a decade, the community became less diverse, with upland areas becoming more similar to lowland ones (Warne et al ., 2020) – suggesting that thermophilisation of communities is not limited to flora – however, this finding was promptly contested (Klimes et al ., 2021).…”
Section: Resultsmentioning
confidence: 99%